If: -4x+3y = 1 Then: 3y = 4x+1 And: y = 4/3x+1/3 which is now in slope-intercept form
4x + 3y=9 x=0 y=3
4x + 3y= 90 -4x -4x _______________ 3y = -4x + 90 /3 /3 ________________ y = -4/3x + 30 hope that helped
x - 3y = 11 So x = 11 + 3y Then, by the other equation, 4x + 3y = -1 becaomes 4(11+3y) + 3y = -1 or 44 + 12y + 3y = -1 or 15y = -45 so that y = -3
(5, 2)
3y = 4x + 9 -4x + 3y = 9 is the standard form
-4x + 3y = 9
3y=4x+9.....-4xAnswer: 4x-3y=9
4x+3y = 12 3y = -4x+12 y = -4/3x+4
4x+3y = 3 3y = -4x+3 y = -4/3x+1 in slope intercept form
3y - 4x = 24 The first step is to write it in the standard form (y=mx + c) 3y = 4x + 24 y = (4x + 24)/3 y = 4x/3 + 8 The y-intercept is 8 and the slope/gradient is 4/3
4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form
If: -4x+3y = 1 Then: 3y = 4x+1 And: y = 4/3x+1/3 which is now in slope-intercept form
y = mx + b 4x - 3y = 3 -3y = -4x + 3 y = 4/3x - 1
Normally, this is a difficult form of the equation to deal with. To change it into a more familiar form, we can do this: 4x + 3y = 0 3y = -4x y = (-4/3)x
4x - 3y = -7 Change all signs: -4x + 3y = 7 Add 4x to both sides: 3y = 4x + 7 Divide both sides by 3: y = (4/3)*x + 7/3 m = 4/3, b = 7/3
4x + 3y=9 x=0 y=3